Pharmacologic safety of oral ivermectin in pregnant women - Esquén Leyva, Carlos (2020)
This study was intended to determine the pharmacological safety of oral ivermectin in pregnant women. A systematic review of information published in the PubMed, MEDLINE, Scopus, Toxline, World Health Organization Clinical Trials Registry, US FDA List, ClinicalTrials, and Cochrane Central Registry databases was conducted from 1990 through 2020. From a total of 73 research articles reviewed, two animal experiments, one clinical and five analytical experiments were studied. Animal studies were found to show that ivermectin was associated with the risk of micarriage, congenital malformations, stillbirth and maternal death. In humans, the effects presented in the animal study could not be determined. It is concluded that clinical studies are necessary to establish the presence of adverse effects in pregnant women from the consumption of ivermectin.